THE EFFECTIVITY OF DUAL FUNDAMENTAL CHARACTERS TRAINING USING BLENDED LEARNING APPROACH TO IMPROVE EARLY CHILDHOOD EDUCATORS' PEDAGOGICAL COMPETENCE - Kosmawan, Heri; Nurhayati, Sri (Jurnal Empowerment, 2025)
The purpose of this study is to determine the Effectivity of two fundamental character training using a blended learning approach for increasing the pedagogical competence of Early childhood educators. The study used quantitative approach and utilized pre-post tests without the use of a control group receiving only one type of treatment. The findings of this study demonstrated effectivity in enhancing the pedagogical competencies of early childhood educators, specifically their ability to analyze, interpret, make decisions, and predict information on a pedagogical scale in preschool age. Enhance the capacity to plan and implement education, particularly the principle of good manners and diligence, at the district/city level through practitioners or training organizers (Education Office, HIMPAUDI partner organization institutions, IGTKI, IGRA, or other SPS). The blended learning implementation pattern is expected to complement and support stakeholders, in this case, the Directorate of Teachers and early age education personnel, in socializing this training as an alternative to preparing competent educators.